The Role of the Mediator in Resolving Fights Between Youth Groups in Malangke District North Luwu Regency - Pabesak, Anthon Sattu; Pasolang, Yoseph (IJBLE Scientific Publications Community Inc., 2024)
This research aims to describe and explain the role of mediators in resolving fights between youth groups in Malangke District, North Luwu Regency. This research uses descriptive qualitative research with data collection techniques through observation, interviews, literature study and documentation. While in managing the data obtained from the research the author uses a qualitative data analysis method with the results of the analysis described descriptively. The results of the research obtained are; 1) Factors that cause fights between groups of teenagers in Malangke Subdistrict are often triggered by trivial things such as; Broken motorbikes, quickly offended, disturbing prayer times, lack of employment, theft and alcohol issues; 2) the role of mediators in efforts to resolve youth group fights, namely; involving government, community leaders, religious leaders, traditional leaders, youth leaders, TNI and Polri to be able to resolve group fights with steps taken by mediators such as; Calling each of the disputing parties to be given religious understanding in accordance with their beliefs; Telling stories that commonly occur so that they can touch the feelings of both parties; Presenting elders or elder figures to solve problems; Visiting the homes of each of the perpetrators and victims to ask what triggers group fights.